(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
The article analyzes university extension as a structuring axis of education, management, and institutional identity in the Fashion Design program at the Federal Institute of Brasília – Taguatinga Campus. The study adopts a qualitative approach based on a case study and examines how extension activities articulate teaching, research, and community engagement, functioning as a social technology for management and learning. Through the analysis of experiences such as Tessitura: Fashion and Literature; Costurando Talentos; Revista Avesso; Quem Vê Look, Não Vê Corre!; and Fashion and Festivals, the study highlights the role of extension in consolidating a dialogical and emancipatory pedagogy grounded in Freirean communication. The findings demonstrate that extension practices strengthen student protagonism, expand dialogue with the local territory, and consolidate fashion as a field of social, cultural, and educational transformation. It is concluded that extension, by weaving together education and management, becomes the guiding thread of the public mission of education, reaffirming Fashion Design’s ethical, aesthetic, and political commitment to diversity, sustainability, and the common good.